Inhibición de Botrytis cinerea en rosas a base de extractos alcohólicos y acuoso de hierba mora ( Solanum Nigrum) - Fiallos Montalvo, Henry Edison (2011)
During the period 2009-2010 research was done on "The Inhibition of Botrytis cinerea on alcoholic and aqueous based extracts of black nightshade (Solanum nigrum) roses." The variable evaluated in Laboratory: Control percentage of Botrytis cinerea in petri dish, whereas the statistical design was evaluated in the variable field: control percentage of Botrytis cinerea on flower buds in Freedom roses variety. This work investigated the inhibition of Botrytis cinerea on roses by applying aqueous and alcoholic extracts of Solanum nigrum and could also be analyzed as biofertilizer for its concentration of minerals.